Contractual Workforce Dilemma: The Intersection of Wage Violations and Sustainable Business Growth in Pakistan’s Textile Sector - Muhammad Faraz; Muhammad Farhan; Kaenat Malik; Muhammad Sufyan Ramish; Qaiser Abbas; Aamir Feroz Shamsi (Al-Qanṭara, 2025)
Purpose: Contractual workers hire in textile and garment industry of Pakistan have high probability to receive wages that may not meet minimum wage standards and overtime payments. This inquiry depicts overtime payment and minimum wage violations among contractual workers observed during social compliance (SC) audits conducted for foreign buyers by social compliance auditors. Such violations have profound consequences for sustained business growth and supply chain sustainability with foreign buyers and often result in termination of purchase orders and prospect trade. The current study intends to investigate the association between hiring contract workers and minimum wage and overtime payment violations Methodology: Fifty-four onsite audit reports on social compliance in export-oriented textile and garment factories in Pakistan were scrutinized. The investigator used the Z test for proportion and the Chi-Square test for association to test the hypothesis. Significance: The present report may help minimize violations reported during the code of conduct audits. This may also ease the suppliers and factories in keeping sustained business growth with foreign retailers and avoid termination of trade, increasing trust and revenue. The current research may also help the factory management and government to make such policies that may help to rectify the existing problem that’s not only violates international labor standards but also Pakistan labor laws.